Clinical evaluation using first-day assessment of patient suitability for successful performance of deep inspiration breath-hold for breast cancer radiotherapy - Bahar Cepni; Vania Batista; Line Hoeltgen; Hanna Waldsperger; Lars Wessel; Jakob Liermann; Semi Harrabi; Fabian Weykamp; Nathalie Arians; Juliane Hörner-Rieber; Jürgen Debus; Eva Meixner (Radiation Oncology, 2026)
Abstract Background Deep inspiration breath-hold (DIBH) is a radiotherapy standard technique for cardiac-sparing in breast cancer, particularly for left-sided tumors. However, not all patients can successfully complete DIBH RT in clinical routine, necessitating conversion to free breathing (FB) techniques and replanning. This study aimed to identify clinical factors predictive of DIBH feasibility to optimize patient selection and resource utilization. Methods This retrospective study analyzed all patients ( n = 1920) who underwent curative postoperative breast cancer radiotherapy at our institution between May 2020 and December 2024. All patients underwent initial DIBH feasibility assessment and were evaluated for completion of radiotherapy with DIBH or conversion to FB technique. A detailed subanalysis was performed for all patients treated in 2023 ( n = 470). Patient-related factors including age, body mass index (BMI), Karnofsky Performance Status (KPS), Charlson Comorbidity Index (CCI), pulmonary comorbidities, smoking status, and geometric surface distance between DIBH and FB planning scans were collected for the subanalysis. Results Across the entire cohort (years 2020–2024) of 1,920 patients, 78 replannings (4%) occurred due to conversion from DIBH to free breathing. Increasing age (cut-off of 63 years) was significantly associated with higher replanning rates ( p = 0.001). In the 2023 subanalysis ( n = 470), pulmonary comorbidities ( p = 0.008), higher CCI ( p = 0.044), and a geometric surface distance of below 1 cm between DIBH and FB CT scans ( p = 0.0001) were significant predictors of replanning. The Karnofsky Performance Score, BMI, and smoking status showed no significant association with replanning. Conclusions Age, pulmonary comorbidities, overall comorbidity burden, and insufficient geometric displacement are significant predictors of DIBH failure in breast cancer radiotherapy. These readily available clinical parameters can optimize patient selection algorithms and inform decisions regarding dual CT simulation workflows. A risk-stratified approach incorporating these factors may reduce unnecessary imaging, decrease planning burden, and improve resource allocation while maintaining optimal cardiac protection for appropriate candidates. Clinical trial number The study was registered in the German Clinical Trials Register (DRKS; registration number: DRKS00038550) on 22 December 2025 ( https://www.drks.de/ ).